2016
DOI: 10.1186/s12879-016-1857-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of high rates of asymptomatic P. vivax infection and very low P. falciparum malaria in Botswana

Abstract: BackgroundBotswana is one of eight SADC countries targeting malaria elimination by 2018. Through spirited upscaling of control activities and passive surveillance, significant reductions in case incidence of Plasmodium falciparum (0.96 – 0.01) was achieved between 2008 and 2012. As part of the elimination campaign, active detection of asymptomatic Plasmodium species by a highly sensitive method was deemed necessary. This study was carried out to determine asymptomatic Plasmodium species carriage by nested PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 34 publications
5
53
0
2
Order By: Relevance
“…The decline in the incidence of Plasmodium falciparum infection has generated enthusiasm for the elimination of malaria. However, there is growing evidence of P. vivax infection in Duffy blood group negative populations (14)(15)(16)(17), and the species shift (18). may jeopardize malaria control efforts.…”
Section: Discussionmentioning
confidence: 99%
“…The decline in the incidence of Plasmodium falciparum infection has generated enthusiasm for the elimination of malaria. However, there is growing evidence of P. vivax infection in Duffy blood group negative populations (14)(15)(16)(17), and the species shift (18). may jeopardize malaria control efforts.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Transmission of P. vivax in these high Duffy-negative regions has been attributed to P. vivax strains circulating among Duffy-positive residents and travelers, or possibly an ape reservoir. [10][11][12] However, recent studies have demonstrated P. vivax infections in Duffy-negative individuals across Africa, including Angola and Equatorial Guinea, 13 Benin, 14 Botswana, 15 Cameroon, 16,17 Ethiopia, 18,19 Western Kenya, 20 Madagascar, 6 Mauritania, 21 and central Sudan 22 (reviewed recently by Zimmerman et al). 23 In addition, standard blood smear microscopy has demonstrated ring-stage formation in infected reticulocytes from Duffy-negative patients, confirming that the P. vivax detected in some cases was invasive and not merely transient merozoites in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…vivax is becoming a serious health problem exhibiting a wide range of hosts children [6], adults [55] and even pregnant women [56]. Also has been detected on asymptomatic individuals [57,58]. The underestimation of P. vivax malaria infections could be attributed to misdiagnosis of the disease using Rapid diagnostic tests RTDs [59], presence of hypnozoite on reservoirs which again cannot be detected using RTDs [60].…”
Section: Previous Studies Onmentioning
confidence: 99%